2003
DOI: 10.1002/jclp.10233
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of trainee impairment in clinical, counseling, and school psychology doctoral programs and internships

Abstract: The purpose of this study was to assess the frequency, type, and management of trainee impairment at a national level across doctoral programs in clinical, counseling, and school psychology and predoctoral internships. A total of 199 surveys were completed, returned, and usable. In general, doctoral programs reported a greater frequency of trainee impairment than internships. However, a greater percentage of internships had a policy and program in place for managing impairments than did doctoral programs. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 11 publications
1
81
0
Order By: Relevance
“…Of the 129 respondents, the yielded rate of problematic students was commensurate with the rate of 1 to 3 problematic students per program reported by Olkin and Gaughen (1991), who only surveyed the faculty. It is worthy to note that Rosenberg and colleagues (2005) asked students about current rates of problematic trainees in their programs, whereas previous studies of training directors have often asked about frequencies over a span of time, such as 5 to 10 years (e.g., Huprich & Rudd, 2004).…”
Section: Review Of Current Research On Student Views Of Peers' Profesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 129 respondents, the yielded rate of problematic students was commensurate with the rate of 1 to 3 problematic students per program reported by Olkin and Gaughen (1991), who only surveyed the faculty. It is worthy to note that Rosenberg and colleagues (2005) asked students about current rates of problematic trainees in their programs, whereas previous studies of training directors have often asked about frequencies over a span of time, such as 5 to 10 years (e.g., Huprich & Rudd, 2004).…”
Section: Review Of Current Research On Student Views Of Peers' Profesmentioning
confidence: 99%
“…Interestingly, Huprich and Rudd (2004) surveyed clinical, counseling, and school psychology doctoral programs and internships and found that only 58% of the doctoral programs reported having a formal program policy in place, but 84% of internships had such a policy. The results, according to the authors, may suggest that programs choose to only invest time in managing issues of student competency when faced with a problem.…”
Section: Training Program Protocols For Handling Issues With Student mentioning
confidence: 99%
“…Gizara and Forrest (2004) explored the importance of the internship as a gatekeeper for quality control in clinical training experiences. Huprich and Rudd (2004) recommended that training programs pay better attention to the assessment and management of problem students. Gaubatz and Vera (2002) compared gatekeeping procedures among counseling programs as to the efficacy of more formalized procedures.…”
Section: The Need For Gatekeepingmentioning
confidence: 99%
“…However, defining personal and professional competence is a subjective and challenging task. The mental health literature reflects this lack of clarity: students with diminished professional functioning have been alluded to as "deficient", "bad", "troublesome", "impaired", "problematic" and "unsuitable" (Forrest, Elman, & Miller, 2008), or identified as experiencing difficulties with alcohol abuse, anxiety and depression, or personality disorders (Huprich & Rudd, 2004).…”
Section: Counseling and Mental Health Programsmentioning
confidence: 99%